2022
DOI: 10.1038/s41467-022-30573-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression signatures of individual ductal carcinoma in situ lesions identify processes and biomarkers associated with progression towards invasive ductal carcinoma

Abstract: Ductal carcinoma in situ (DCIS) is considered a non-invasive precursor to breast cancer, and although associated with an increased risk of developing invasive disease, many women with DCIS will never progress beyond their in situ diagnosis. The path from normal duct to invasive ductal carcinoma (IDC) is not well understood, and efforts to do so are hampered by the substantial heterogeneity that exists between patients, and even within patients. Here we show gene expression analysis from > 2,000 individually… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…Ductal carcinoma in situ (DCIS) is a non-obligate precursor of invasive ductal carcinoma, which can develop into invasive disease, the treatment of which often involves surgical removal of the lesion and radiotherapy (Wilson et al 2022). Because not all DCIS lesions progress to invasive disease, there is great interest in understanding the molecular mechanisms underpinning invasiveness in DCIS, which are currently not well known (Wilson et al 2022, Rebbeck et al 2022), but could help to guide better therapeutic strategies. Our goal was to use Xenium and scFFPE-seq data to identify different tumor subtypes and supplement H&E imaging and pathology with molecular targets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ductal carcinoma in situ (DCIS) is a non-obligate precursor of invasive ductal carcinoma, which can develop into invasive disease, the treatment of which often involves surgical removal of the lesion and radiotherapy (Wilson et al 2022). Because not all DCIS lesions progress to invasive disease, there is great interest in understanding the molecular mechanisms underpinning invasiveness in DCIS, which are currently not well known (Wilson et al 2022, Rebbeck et al 2022), but could help to guide better therapeutic strategies. Our goal was to use Xenium and scFFPE-seq data to identify different tumor subtypes and supplement H&E imaging and pathology with molecular targets.…”
Section: Resultsmentioning
confidence: 99%
“…This is illustrated in our study using an FFPE block from a patient breast biopsy that contains both ductal carcinoma in situ and invasive ductal carcinoma. In this model, DCIS refers to neoplastic epithelial cells that remain confined within the ducts, and DCIS is therefore considered nonlethal (Allred 2010, Rebbeck et al 2022, Wilson et al 2022). DCIS can be (albeit is not always) the immediate precursor of potentially lethal invasive ductal carcinoma, when the ductal morphology is broken down and cancerous cells invade the stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent comprehensive profiling paper identified that the biggest microenvironment change from normal to DCIS was in the myoepithelial component 81 . In contrast, the greatest distinction between DCIS and IDC was the stroma, including signatures of cancer‐associated fibroblasts and collagen deposition, supported by a large RNA sequencing study 82 . Intriguingly, DCIS with a more ‘normal’‐appearing myoepithelium was more likely to progress to invasive carcinoma 81 .…”
Section: Proposed Mechanisms For the Development Of Invasive Breast C...mentioning
confidence: 99%
“…Ductal carcinoma in situ (DCIS), a subtype of BC where atypical epithelial cells are restricted to the milk ducts, is considered a non-invasive or pre-invasive as well as a non-obligate precursor to IDC [ 8 , 9 ]. An important proportion of patients with BC emphasize the co-existence of IDC with DCIS (IDC-DCIS) [ 10 ]; women with DCIS experience higher long-term risk of IDC and death from BC than women in the general population [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…An important proportion of patients with BC emphasize the co-existence of IDC with DCIS (IDC-DCIS) [ 10 ]; women with DCIS experience higher long-term risk of IDC and death from BC than women in the general population [ 11 ]. However, many women with DCIS will probably never progress to IDC [ 8 ], so that it remains a great challenge to determine which patients should be over-treated, or which need to be monitored without aggressive therapy [ 12 ]. Considering that the molecular continuum from normal duct to IDC, passing through atypical ductal hyperplasia (ADH) and/or DCIS, is still not well understood [ 8 ], the finding of novel molecular biomarkers of BC progression is absolutely necessary for developing prediction models to avoid the underestimation of IDC [ 13 ] and, consequently, to assure more adequate patient diagnosis and treatment [ 9 ].…”
Section: Introductionmentioning
confidence: 99%